2016
DOI: 10.1007/s13346-016-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarriers for spleen targeting: anatomo-physiological considerations, formulation strategies and therapeutic potential

Abstract: There are several clinical advantages of spleen targeting of nanocarriers. For example, enhanced splenic concentration of active agents could provide therapeutic benefits in spleen resident infections and hematological disorders including malaria, hairy cell leukemia, idiopathic thrombocytopenic purpura, and autoimmune hemolytic anemia. Furthermore, spleen delivery of immunosuppressant agents using splenotropic carriers may reduce the chances of allograft rejection in organ transplantation. Enhanced concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 102 publications
(114 reference statements)
0
18
0
Order By: Relevance
“…Tumor endothelial cells (TECs) are genetically more stable than tumor cells (TCs) and this decreases the resistance to chemotherapeutic drugs. 19) In addition, TECs represent only a small fraction of the tumor, which decreases the dose of drugs needed compared with delivery to TCs. Unfortunately, there is no specific affinity of drugs and NPs for endothelial cells.…”
Section: Lnps For Gene Delivery To Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor endothelial cells (TECs) are genetically more stable than tumor cells (TCs) and this decreases the resistance to chemotherapeutic drugs. 19) In addition, TECs represent only a small fraction of the tumor, which decreases the dose of drugs needed compared with delivery to TCs. Unfortunately, there is no specific affinity of drugs and NPs for endothelial cells.…”
Section: Lnps For Gene Delivery To Endothelial Cellsmentioning
confidence: 99%
“…Generally, systemically administered LNPs carrying nucleic acids can access organs in which the capillaries are characterized by the presence of pores or fenestrations such as the liver and spleen. [17][18][19] Parenchymal cells in these two organs are thus considered accessible to LNPs, which make them particularly interesting candidate organs for gene therapy. The liver has received the most attention so far, and several lipid formulations are in different clinical trial stages.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been reported that the spleen receives barely 15% of the i.v. injected dose of nanomedicines [83]. Therefore, additional surface modification strategies may be needed for applications that require splenic accumulation of PLGA particles.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless,the successful protein and mRNAd elivery to the lung or spleen opens up awide range of possibilities for novel treatments of diseases. [28] Theu nderlying mechanisms are not clear at this stage.W eenvision that further structure-activity relationship studies on how LNPs interact with biological systems can shed some light on this issue.…”
Section: Angewandte Chemiementioning
confidence: 98%